PERCERAIAN DI PENGADILAN AGAMA PAMEKASAN: ANALISA TERHADAP ALASAN DAN FAKTOR CERAI GUGAT PADA TAHUN 2019 - Imam Hafas (Universitas Islam Malang, 2022)
In the case of marriage, divorce become one of the indications that are able to damage the bond of marriage. The Religious court Pamekasan is the realm of the law in terms of finishing a case, one of them is a divorce case that in 3 years has increased significantly. Namely by the existence of reasons that cause the dominant as well as the factors that affect the attitude of the wife to initiate divorce (contested divorce) in Pamekasan?. The method in this research is qualitative, namely field research (field research) with the sociological approach. The use of primary data sources and secondary data collection through observation, interview, and documentation. Analysis of the data by the method of descriptive analysis of the wear groove of thinking inductive. The results of the study show that the divorce case is dominated by the quran and sunnah based on the reasons that dominate, namely the growth of disharmony in the form of disputes and quarrels which is motivated by several reasons, namely the absence of responsibility, the presence of third parties, and the presence of immoral actions and the presence of an arranged marriage or forced marriage and the increasing awareness of the women on a role and rights in the family setting and the response of the extension with carry out some activities, such as seminars in the form of guidance premarital counseling premarital, and the granting of understanding, either persuasive or through the assembly of the building that existed under the auspices of the religious educator.